Magnetospheric gamma-ray emission in active galactic nuclei - Katsoulakos, Grigorios; Rieger, Frank M. (The astrophysical journal, 2018)
The rapidly variable, very high-energy (VHE) gamma-ray emission from active galactic nuclei (AGNs) has been frequently associated with non-thermal processes occurring in the magnetospheres of their supermassive black holes. The present work aims to explore the adequacy of different gap-type (unscreened electric field) models to account for the observed characteristics. Based on a phenomenological description of the gap potential, we estimate the maximum extractable gap power L gap for different magnetospheric setups, and study its dependence on the accretion state of the source. L gap is found in general to be proportional to the Blandford-Znajek jet power L BZ and a sensitive function of gap size h, i.e., , where the power index is dependent on the respective gap setup. The transparency of the vicinity of the black hole to VHE photons generally requires a radiatively inefficient accretion environment and thereby imposes constraints on possible accretion rates, and correspondingly on L BZ. Similarly, rapid variability, if observed, may allow one to constrain the gap size . Combining these constraints, we provide a general classification to assess the likelihood that the VHE gamma-ray emission observed from an AGN can be attributed to a magnetospheric origin. When applied to prominent candidate sources these considerations suggest that the variable (day-scale) VHE activity seen in the radio galaxy M87 could be compatible with a magnetospheric origin, while such an origin appears less likely for the (minute-scale) VHE activity in IC 310.
Gesehen am 15.04.2020